Study on the leakage dispersion law of exposed high-pressure natural gas pipelines in the mountainous environment - Xu, Duo; Chen, Liqiong; Zhan, Wenwen; Zhang, Kai; Lu, Jingyang; Ji, Yongqiang; Ma, Rufei (Frontiers in Energy Research, 2023)
The pipelines in mountainous areas have complex terrain conditions and pass through many densely populated areas. Once a pipeline leakage accident occurs, it will cause serious damage to the surrounding people and the environment. In this paper, a leakage diffusion model of a bare natural gas pipeline is established for the exposed leakage scenario, and a simulation scheme is established according to the characteristics of pipeline laying and environmental characteristics in mountainous areas. Research has been carried out on the diffusion pattern and the influence range of exposed gas transmission pipeline leaks under four types of factors: different leak apertures, ambient wind speed, mountainous obstacle conditions, and mountainous laying environment. The dangerous range formed by gas diffusing along the ground and high altitude under different scenarios and the influence law of different influencing factors on the dangerous range are obtained, and suggestions for emergency rescue focus areas and emergency response strategies have been given. The research conclusions can provide a theoretical basis for emergency response strategies for exposed leakage accidents of high-pressure natural gas pipelines in mountainous environments, and are of great significance to the quantitative analysis of the risk consequences of natural gas pipelines.